Dust Accumulation and Aggregation on Pv Panels: An Integrated Survey on Impacts, Mathematical Models, Cleaning Mechanisms, and Possible Sustainable Solution - Khalid, H (Elsevier Ltd, 2023)
Photovoltaic (PV) panels are one of the most emerging components of renewable energy integration. However, where the PV systems bring power conversion efficiency with its bulk installation setup and eco-friendly feasibility, it also brings the factors that could hamper the performance and efficiency of the system. One of these dependent factors is the accumulation of dust particles and its aggregation which could significantly influence the effect of PV systems. The dust can accumulate in its various forms of soiling by fusing with other environmental variations like rain, storm, and humidity. To resolve these challenges which could impact the energy yield of PV systems, the impact of dust as well as effective cleaning mechanisms are required to be studied to restore the performance and power generation output. In this article, an integrated survey of (1) possible factors of dust accumulation, (2) dust impact analysis, (3) mathematical model of dust accumulated PV panels, and (4) proposed cleaning mechanisms discussed in the literature, and (5) a possible sustainable solution for PV systems to survive in this dust accumulated environment are presented. This study also represents handy information to readers, engineers, and practitioners on the development phase of various technologies involved in minimizing the impact of dust accumulation by its removal, adequate cleaning, and restoration. It also addresses the future possible challenges of these cleaning mechanisms. A comprehensive list of publications to date in the open literature is thereby compiled to canvas a complete visual of the different developments in this area. © 2023 International Solar Energy Society